(untitled) (Sociologisk Forskning, 1996)
This article sets out to examine the language used in the public discourse on the economy in Sweden. We investigate the metaphors used by economists in public discourse, and show how they function to depoliticize economic policy making. Theoretically, we introduce the notion of ’the surplus value of metaphors’ and by this, we develop the connection between metaphor and myth. We also try to show how myths mask themselves as common sense. Finally, we argue that the economic profession has difficulties in conceptualizing the contingent and rapidly changing economic developments in contemporary society, and that the common sense metaphors function to construct sense while failing to provide explanation.